Visual and Surface Properties of CdTe Thin Films on CdS/FTO Glass Substrates - Ramya K; Yuvaraja T (Institute of Advanced Engineering and Science, 2016)
Cadmium telluride (CdTe) thin film material was deposited ontop of Cadmium Sulfide (CdS) substrate using vacuum evaporation technique. The sample was characterized using X-ray diffraction(XRD) and UV-VIS-NIR spectroscopy. XRD studies revealed that the sample was polycrystalline in nature. The SEM image showed that the sample is columnar in structure and the grains are uniform. Optical band gap of the CdTe thin film was estimated from transmittance and reflectance data and it was found 1.53eV.The structural, optical and surface properties of the film showed that the CdTe thin film materials can be used for fabrication of CdTe thin film solar cell.